Applying The New Ecological Paradigm Scale in the Case of Environmental Education: Qualitative Analysis of the Ecological Worldview of Dutch Children (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
Greater interest in environmental education or EE has emerged as even short educational programs were proved to stimulate environmental awareness in children (Manoli et al, 2007) and college students (Rideout, 2005). However, the efficacy of environmental education was rarely tested. While the measurements tackling environmental knowledge, attitudes and behaviour were developed in publications of the Journal of Environmental Education, Journal of Environmental Psychology,  Environment and Behavior and Environmental Education Research, practically none have been applied to the case of environmental education. State-of-the-art in environmental education research is dominated by quantitative studies characterized by uniform, standardized models that do not take socio-cultural context in which education occurs into account.